The Planning of Trials of New Drugs in Pulmonary Tuberculosis - Scadding, J. G. (Methods of Information in Medicine, 1962)
The clinical investigation of a new drug in tuberculosis needs a comparative trial, in which patients with a defined type of disease are allocated to two or more treatment regimes. The trial will often be most effectively conducted on a co-operative basis at a number of hospitals. Such a trial needs an organising committee, of which a statistician is an essential member; the preparation by this committee of a detailed protocol and of appropriate record forms; a group of co-operating clinics and hospitals; preferably at least one meeting of the clinicians from these clinics and hospitals to discuss and approve the protocol; agreed laboratory procedures, and sometimes special provision of laboratory facilities; and assessment of results as objectively as possible, by bacteriological results, including the rate of emergence of resistant organisms, by consideration of toxic and other untoward effects of the drugs, and by the examination of serial radiographs by independent assessors, unaware of treatment-groups.Die klinische Erprobung eines neuen Heilmittels gegen Tuberkulose erfordert eine Vergleichsprüfung, in der Patienten eines bestimmten Krankheitstypus sich zwei oder mehreren verschiedenen Behandlungsarten unterziehen müssen. Es wird oft zweckmäßig sein, den Versuch in Zusammenarbeit mehrerer Krankenhäuser durchzuführen. Dazu bedarf es einer Planungsgruppe, zu der notwendig auch ein Statistiker gehört; der Ausarbeitung eines genauen Protokolls und geeigneter Krankengeschichten; einer Gruppe zusammenarbeitender Kliniken und Krankenhäuser; zumindest einer Zusammenkunft der beteiligten Ärzte zur Besprechung und Festlegung des Protokolls; aufeinander abgestimmter Laboratoriumsmethoden, zuweilen auch der Bereitstellung besonderer Laboratoriumseinrichtungen und einer möglichst objektiven Bewertung der Ergebnisse durch bakterielle Befunde einschließlich des Auftretens resistenter Organismen, durch Feststellung toxischer oder anderer Nebenwirkungen der Präparate und durch Auswertung serienmäßiger Röntgenaufnahmen seitens unabhängiger Untersucher, denen die Art der Behandlung nicht bekannt ist.